2012
DOI: 10.1097/wox.0b013e3182439613
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Antioxidant Defense

Abstract: Reactive oxygen species (ROS) are produced by living organisms as a result of normal cellular metabolism and environmental factors, such as air pollutants or cigarette smoke. ROS are highly reactive molecules and can damage cell structures such as carbohydrates, nucleic acids, lipids, and proteins and alter their functions. The shift in the balance between oxidants and antioxidants in favor of oxidants is termed “oxidative stress.” Regulation of reducing and oxidizing (redox) state is critical for cell viabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

52
2,816
1
102

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 3,979 publications
(2,971 citation statements)
references
References 139 publications
52
2,816
1
102
Order By: Relevance
“…In fact lipid peroxidation products have been used as indirect biomarkers of oxidative stress with aging [30]. According to [31], there is a great deal of interest in lipid peroxidation in terms of evaluating its importance as a primary mechanism of tissue injury and deterioration of a wide variety of cellular enzymes resulting in neurodegenerative process.…”
Section: Discussionmentioning
confidence: 99%
“…In fact lipid peroxidation products have been used as indirect biomarkers of oxidative stress with aging [30]. According to [31], there is a great deal of interest in lipid peroxidation in terms of evaluating its importance as a primary mechanism of tissue injury and deterioration of a wide variety of cellular enzymes resulting in neurodegenerative process.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported that when, either depletion of antioxidants or accumulation of ROS (pro-oxidant and antioxidant imbalance) occur, cells attempt to counteract the pro-oxidant effect and restore the red-ox balance by activation or silencing of genes encoding defensive enzymes, transcription factors, and structural proteins 14,36 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, increase in SOD is invariably followed by an increase in CAT, since SOD is primary enzyme account for dismutation of superoxide to H 2 O 2 . Subsequently, H 2 O 2 is reduced by CAT to oxygen and water 14 . In contrary, the increase in MDA and 8OHd Gconcentration always followed by the decrease in the activity of SOD and CAT or vice versa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations